Práticas e discursos comunicacionais na interface web: sites das agências de cooperação internacional na Amazônia legal - Assumpção, Douglas Junio Fernandes (2018)
This thesis analyzes the communication practices on the web of the International Cooperation Agencies (ICA) in the Legal Amazon, with the purpose of establishing the conditions in which the Environment websites, especially those that produce content about the Amazon, that use the communicational interfaces as a form of informational dissemination. The research has as a starting point the way the Amazon is represented in the websites of these agencies, asking if their aspect of representation is real or fanciful. Thus, in this material, attention is focused on explaining the Amazon region, succinctly locating it in time and space, in order to understand the economic profile, power relationship and the stereotype produced by the media. In order to delimit the sites, it was necessary to analyze the survey conducted by Pressler (2010), addressing a classification of ICA. From this classification, the sites of the following institutions are evaluated: Institute of Man and Environment of the Amazon (IMAZON); Real Amazon; Greenpeace and Conservation International Brazil. The observation model applied in the thesis is based on the use, in the first moment, of the technique of heuristic analysis of Nielsen (2000), that allows to know a process of detailed appreciation of the interface. In the second moment, the application of the technique of content analysis of Bardin (1997), that allows the identification of the communication categories and contextualization of communication strategies of these sites. And in the third moment, the use of the Discourse Analysis of Charaudeau (2010). The site categorization process examines the approaches to the environment and the Amazon, in order to verify the communication strategies and communicational processes that exist in the interfaces. In this way, the content of the sites is delimited by analyzing the communicational elements applied to the visual composition and the multimedia resources so that they can legitimize them as a channel of approximation, knowledge and information with its public..